Genetic and Heterosis Analyses using Hayman's Six‐Generation Model for Grain Yield and Yield Components in Maize. Issue 3 (1st May 2015) - Chen, H.M.; Zhang, Y.D.; Jiang, F.Y.; Huang, Y.X.; Yao, W.H.; Chen, X.H.; Kang, M.S.; Fan, X.M.
ABSTRACT: This study aimed to (i) estimate additive ( a ), dominance ( d ), aa, ad, and dd genetic variances and effects; (ii) investigate the differences for five genetic variances or effects among crosses between a maize ( Zea mays L.) line from the Suwan‐1 heterotic group and five inbred lines from other groups; and (iii) develop a theory to explain the results from Hayman's model and low‐, mid‐, and high‐parent heterosis. Hayman's model was used to evaluate the genetic effects in five six‐generation sets between the Suwan‐1 cross with five lines from other groups. The magnitude of variance was consistent among all crosses for grain yield (GY) and ear length (EL) but different for ear diameter (ED), row number per ear (RE), kernel number per row (KR), and 100‐kernel weight (KW). The a, d, aa, ad, and dd effects were similar for EL among crosses between lines from different groups, indicating that the effects for EL could be used to differentiate Reid and non‐Reid heterotic groups. We postulated a 'linked coexpressed genes' (LCG) model to (i) explain why a, d, aa, ad, and dd variances and effects might be different when a common line is crossed with other lines and (ii) serve as an improved model explaining heterosis. The LCG model explains what dominance–overdominance theories can explain and explains what dominance–overdominance models do not. For example, it can explain why an inbred line cannot perform like a hybrid and why an F2 population for a quantitative trait has a normal distribution.